Pengaruh E-Service Quality dan Perceived Value Terhadap Customer Satisfaction Pengguna Aplikasi Flip : (Studi pada Mahasiswa Aktif S-1 dan D-4 Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta) - Amelia Salsa Sabila; Eka Faradila Yasmin; Salma Rahmadani; Saski Aulia; Umi Widyastuti; Destria Kurnianti (Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to analyze the effect of E-Service Quality and Perceived Value on Customer Satisfaction in using the Flip application. This study uses quantitative methods by collecting data through a Likert scale questionnaires distributed to active S-1 and D-4 students of the Faculty of Economics and Business State University of Jakarta who are Flip application users. The sampling method applied is purposive sampling, with a final sample of 86 respondents. The data collected was then analyzed using multiple linear regression with the help of SPSS software. The results showed that the two independent variables, namely E-Service Quality and Perceived Value, had a significant positive effect on Customer Satisfaction, both partially and simultaneously. E-Service Quality has a more dominant influence than Perceived Value with a regression coefficient of 0,379. This finding indicates that efficient, reliable, and high-value digital services contribute significantly to increasing Flip user satisfaction.